Analisis perbandingan rencana strategis perusahaan pegadaian di Indonesia - Jauhari, Ahmad (Maliki Interdisciplinary Journal, 2024)
This article presents a comparison of the strategic plans of three pawnshop companies: PT. Pegadaian Persero, PT. Pesonna Optima Jasa, and PT. Pegadaian Galeri 24. These three pawnshops have different objectives and success strategies. PT. Pegadaian Persero focuses on increasing economic and social value, enhancing customer experience, product and customer diversification, sustainable innovation, and capacity development. PT. Pesonna Optima Jasa aims to improve the company's performance in terms of revenue and profit, particularly through the development of the core business and in the segments of labor supply and other services. Meanwhile, PT. Pegadaian GALERI 24 places a greater emphasis on business acceleration, market expansion, productivity, efficiency, and a sustainable future. In summary, these three pawnshops have distinct strategic plans to achieve their goals, with PT. Pegadaian GALERI 24 having the most detailed and comprehensive strategic plan.